Tumour response to hypoxia: understanding the hypoxic tumour microenvironment to improve treatment outcome in solid tumours - Bigos, Kamilla JA.; Quiles, Conrado G.; Lunj, Sapna; Smith, Danielle J.; Krause, Mechthild; Troost, Esther GC.; West, Catharine M.; Hoskin, Peter; Choudhury, Ananya (Frontiers in Oncology, 2024)
Hypoxia is a common feature of solid tumours affecting their biology and response to therapy. Key to this is the hypoxia-inducible factor (HIF), orchestrating gene expression involved in crucial tumour processes-proliferation, angiogenesis, immune evasion, metabolic reprogramming, extracellular matrix (ECM) remodelling, and cell migration. This can negatively impact patient outcomes by inducing therapeutic resistance. The importance of hypoxia is clearly demonstrated by continued research into finding clinically relevant hypoxia biomarkers, and hypoxia-targeting therapies. One of the problems is the lack of clinically applicable methods of hypoxia detection, and lack of standardisation. Methods of detecting hypoxia do not take into consideration the complexity of the hypoxic tumour microenvironment (TME). Therefore, this needs further elucidation as 50% of solid tumours are hypoxic. The ECM, shaped by cancer-associated fibroblasts (CAFs) and tumour cells, plays a pivotal role, particularly in fibronectin, collagen, and hyaluronic acid fibres, crosslinked by enzymes like lysyl oxidase. HIFs influence this, impacting tumour stiffness and fibrosis, but there are inconsistences in the role of matrix stiffness in therapeutic resistance. Further research is needed into identifying different CAF subtypes and their exact roles; with some showing pro-tumorigenic capacity and others having anti-tumorigenic roles.This has made it difficult to elucidate the role of CAFs within the TME. However, it is an important area of research that requires unravelling as current strategies to target CAFs have resulted in worsened prognosis. The role of immune cells within the tumour microenvironment is also discussed as hypoxia has been associated with modulating immune cells to create an anti-tumorigenic environment. This lead to development of immunotherapies. These hypoxia-induced changes can confer resistance to conventional therapies including chemotherapy, radiotherapy and immunotherapy. This review summarizes the current knowledge on the impact of hypoxia on the TME and its implications for therapy resistance. It also discusses the potential of hypoxia biomarkers as prognostic and predictive indictors of treatment response, as well as the challenges and opportunities of targeting hypoxia in clinical trials.